Jordan 2024 - Jackson, Anthon; Ruffin, Jason; Stafford, Paul; Tabbaa, Sanad (Lonely Planet guidebooks., 2024)
Discover popular and off the beaten track experiences from seeing the magnificent Rose City of Petra, to learning about Jordan's past through the ancient art of mosaic making, and bathing in the mineral rich waters of the Ma'in hot springs.